Kiracının Ölümünün Her Türlü Kira İlişkisine Etkisi ve Bu Etkinin Özellikle Konut ve Çatılı İşyeri Kiraları Bakımından Gösterdiği Özellikler - (:unkn) unknown (My University, 2017)
Bu çalışmada, kullandırma borcu doğuran sözleşmelerden olan kira sözleşmelerinde, sözleşme taraflarından biri konumundaki kiracının ölümünün kira sözleşmelerine etkisi ele alınmıştır. Kiranın genel hükümlerine tâbi kira sözleşmelerinde kiracının ölümü halinde kira sözleşmesi son bulmayıp, kira sözleşmesi kiracının mirasçıları ile devam etmektedir. Kiraya veren, kiracısının ölümü üzerine sözleşmeyi feshedemez. Konut ve çatılı işyeri kiraları söz konusu olduğunda ise, kiracının ölümüne bağlanan sonuç farklıdır. Bu tip kiralarda, kiracının ölümü üzerine, konut kiralarında kiracı ile birlikte oturanlar, çatılı işyeri kiralarında ise ölen kiracının ortakları ya da bu ortakların aynı meslek ve sanatı yürüten mirasçıları, kira sözleşmesini sürdürebilirler. Konut ve çatılı işyeri kiralarında ölen kiracının mirasçıları, külli halef sıfatları gereği kiracı olamazlar. Türk Borçlar Kanununun 356. maddesi bir özel intikal kuralı getirdiğinden, ölen kiracının kira sözleşmesinden doğan kullanım hakkı terekesi içerisinde yer almaz ve bu sebeple mirasçılarına da intikal etmez

The aim of this study, is to focus on the impact of the death of the lessee who is one of the parties, in a lease contract. The lease contract is accepted as a form of a usage contract. According to the lease contracts that are regulated under the “General Clauses Of The Lease Contract” of the Turkish Code of Obligations, if a lessee dies, the lease contract does not end and it continues with the inheritors of the lessee. The lessor on the contrary; does not have the right to annul the above mentiond contract. However when the lessee in a “Lease Contract of the Residence and The Roofed Place of Business” passes away, the impact is quite different. In a lease contract belonging to the afore said articles; upon the death of the lessee, the people living all together with the late lessee may go on with the residence lease contract and the co-partners of the late lessee and the inheritors of the co-partners dealing with the same profession and art may go on with the roofed place of business lease contract. The inheritors of the deceased lessee of a lease contract of the residence and the roofed place of business, do not become the new lessees because of their consecutive successor roles. The Article 356 of the Turkish Code of Obligations regulate a special inheritance rule, and followingly the usage right of the late lessee that arises from the lease contract does not take place in his estate and that is the reason why his lessee position is not perceived by the inheritors of the deceased lessee
Keywords: Hukuk